The Secret Geographer: Thinking Aloud on Legal Engagements in Scholar-Activism - Brickell, Katherine; Jeffrey, Alex; McConnell, Fiona; Ahearn, Ariell; Calkin, Sydney; Klosterkamp, Sarah (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
The award-winning and best-selling book The Secret Barrister (2018) took the general public into the unfamiliar space of the courtroom. Inspired both by its candour and illumination of the legal world and its proceedings, this roundtable reveals some of the hidden stories of geographers, including ourselves, who are engaged in scholar-activism in law. The roundtable comprises four conversations and takes the reader into a range of legal realms in and beyond the courtroom. It explores geographers’ professional/personal experiences of navigating these spaces, the actors present in them, and the wider political terrains in which they sit. The conversations evidence the ‘shape-shifting’ of identities, disciplinary and institutional affiliations, and positionalities dependent on audience, insider/outsider status, place, and (political) goal. By going ‘behind the scenes’ the roundtable also offers new insights into how explicitly or outwardly ‘activist’ geographers are able or want to be in their scholar-activism in law. Activism tends to be understood as an intentional, planned-for, and public endeavour, yet the roundtable tells a more nuanced story. Honing in on the legal reveals experiences of scholar-activism that are also accidental, unexpected, and private, but which, we argue should equally ‘count’ and be ‘counted’ as examples of meaningful geographical engagement with social justice movements and endeavours. Ultimately, our coming together in the roundtable is solidaristic in aim. It arises from a collective desire for connection in an academy which has yet to grapple with what it means to support geographers in their justice-oriented legal endeavours. By beginning to unshroud the secrecy of such endeavours in geography, we hope the roundtable inspires others to think more and potentially share more on their varied legal engagements in scholar-activism moving forward.